Impacto ambiental del sistema de alcantarillado sanitario de la ciudadela “El Guayacán” Cantón Quevedo, año 2015 - Torres Segarra, Carlos Vicente (2016)
The study was based on analysis on the generation of environmental impacts to the physical, biotic and socioeconomic backgrounds of the sanitary sewer system en the Citadel "El Guayacán", proving the obsolescence of public service to the community and the degree of involvement measured in LEOPOLD matrix. Two environmental problems could be identified by assessing LEOLOPD matrix, one that affects the quality of life of the inhabitants of the citadel and other water pollution of two rivers, especially the river Quevedo, this is due to lack of preventive maintenance of sanitary sewer system, which controls the generation of infectious vectors that cause diseases such as zika, chikungunya, dengue, with its serious consequences. Due to lack of resources, it proposes a plan for environmental monitoring and operation, which must be accepted by the local authorities to ensure the health of its population, with the participation of all involved to achieve the objective 3 of the Plan of Good Living.